Glucose concentration sensor and preparation method thereof
By designing a glucose concentration sensor including a substrate, gallium nitride layer, aluminum nitride layer, organic functional group layer and metal electrode layer, the problems of high testing cost, cumbersome process and low sensitivity in the existing detection methods are solved, and the problem of high testing costs, cumbersome process and low sensitivity are achieved. Efficient and sensitive glucose concentration detection.
Patent Information
- Application Number
- CN202411454495.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing glucose concentration detection methods have problems such as high testing costs, cumbersome testing process and low sensitivity.
A glucose concentration sensor is designed, including a substrate, gallium nitride layer, aluminum nitride layer, organic functional group layer and metal electrode layer. The electrical signal when the organic functional group layer and glucose molecules are obtained through two-dimensional electron gas to indicate glucose The concentration of the molecule.
It improves the detection efficiency and sensitivity of glucose concentration sensors, reduces detection costs, and simplifies the detection process.
Smart Images

Figure CN119470576A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of analysis and detection, and in particular to a glucose concentration sensor and a preparation method thereof. Background Art
[0002] Glucose is the most widely distributed monosaccharide in nature. As the main energy source for living cells, glucose can not only effectively enhance human memory, but also stimulate calcium absorption and promote communication between cells. However, an imbalance in the concentration of glucose in the blood may cause a series of diseases; for example, low glucose concentration may cause symptoms such as fatigue, dizziness and easy fatigue; while high glucose concentration may cause dehydration, diabetic nephropathy, diabetic foot and other problems.
[0003] At present, glucose concentration detection is mainly achieved through spectroscopy, fluorescence and colorimetry.
[0004] However, spectroscopy, fluorescence and colorimetry usually have problems such as high detection reagent cost, high equipment cost, complex equipment, cumbersome testing process and low sensitivity. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a glucose concentration sensor and a preparation method thereof, so as to solve the problems of high testing cost, complicated testing process and low sensitivity in the existing glucose concentration detection method.
[0006] In order to solve the above problems, the present invention is achieved through the following technical solutions:
[0007] The present invention provides a glucose concentration sensor, which includes a substrate, a gallium nitride layer, an aluminum nitride layer, an organic functional group layer and a metal electrode layer;
[0008] The substrate comprises at least one isosceles trapezoidal structure; adjacent isosceles trapezoidal structures are spaced by a first length; the isosceles trapezoidal structure comprises a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are waists of the isosceles trapezoidal structure; the third side surface is opposite to the fourth side surface and is perpendicular to the top surface;
[0009] The gallium nitride layer is epitaxial on the first side surface and the second side surface; the aluminum nitride layer is stacked on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure; the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas, and the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined; the electrical signal is used to indicate the concentration of the glucose molecule;
[0010] The organic functional group layer is stacked on the upper surface of the aluminum nitride layer; the organic functional group layer includes a first region close to the third side and a second region close to the fourth side, and the first region and the second region are spaced apart by a second length;
[0011] The metal electrode layer includes a first electrode layer and a second electrode layer, the first electrode layer is stacked in the first region and extends to the aluminum nitride layer along the plane where the third side is located, and the second electrode layer is stacked in the second region and extends to the aluminum nitride layer along the plane where the fourth side is located.
[0012] The present invention also provides a method for preparing a glucose concentration sensor, the method comprising:
[0013] Obtain a substrate; the substrate comprises at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced by a first length; the isosceles trapezoidal structure comprises a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are waists of the isosceles trapezoidal structure; the third side surface and the fourth side surface are opposite and perpendicular to the top surface;
[0014] epitaxially growing a gallium nitride layer on the first side surface and the second side surface;
[0015] An aluminum nitride layer is grown on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure, and the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas; the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined; the electrical signal is used to indicate the concentration of the glucose molecule;
[0016] Spin coating a first solution on the upper surface of the aluminum nitride layer, and drying the first solution spin-coated on the aluminum nitride layer to obtain an organic functional group layer; the organic functional group layer includes a first region close to the third side surface and a second region close to the fourth side surface, and the first region and the second region are spaced apart by a second length;
[0017] A first electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the first area and the third side are located, and a second electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the second area and the fourth side are located, to obtain a glucose concentration sensor; the first electrode layer and the second electrode layer constitute a metal electrode layer of the glucose concentration sensor.
[0018] Compared with the prior art, the embodiments of the present invention include the following advantages:
[0019] The glucose concentration sensor provided by the embodiment of the present invention includes a substrate, a gallium nitride layer, an aluminum nitride layer, an organic functional group layer and a metal electrode layer; wherein the substrate includes at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced apart by a first length, and the two-dimensional electron gas and the organic functional group layer stacked in sequence on each isosceles trapezoidal structure have a large specific surface area, which increases the contact probability between the glucose molecules and the organic functional group layer, and improves the detection efficiency of the glucose concentration sensor; the gallium nitride layer is epitaxial on the first side and the second side of the isosceles trapezoidal structure, and the aluminum nitride layer is stacked on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure, so that the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas, and the organic functional group layer is stacked on the upper surface of the aluminum nitride layer. The first electrode layer of the metal electrode layer is stacked on the first area of the organic functional group layer, and extends to the aluminum nitride layer along the plane where the third side of the isosceles trapezoidal structure is located, and the second electrode layer of the metal electrode layer is stacked on the second area, and extends to the aluminum nitride layer along the plane where the fourth side is located; the electron concentration of the two-dimensional electron gas layer is sensitive to weak electrical signals, and can obtain weak electrical signals before and after the specific binding of the organic functional group layer and the glucose molecule in real time, and output electrical signals through the metal electrode layer, thereby reducing the detection limit of glucose concentration and improving the sensitivity of the glucose concentration sensor; further, the organic functional group layer is directly stacked on the surface of the aluminum nitride layer, which can shorten the distance between the organic functional group layer and the two-dimensional electron gas, and further improve the sensitivity of the glucose concentration sensor. The glucose concentration sensor provided by the embodiment of the present invention has a simple structure and is easy to operate. While improving the detection sensitivity of glucose concentration, it also reduces the detection cost of glucose concentration.
[0020] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 is a schematic diagram of a top view of a glucose concentration sensor provided by an embodiment of the present invention;
[0022] Figure 2 is a schematic diagram of a cross-sectional structure of a glucose concentration sensor provided by an embodiment of the present invention along the thickness direction of the glucose concentration sensor;
[0023] Figure 3 is a flowchart of the steps of a method for preparing a glucose concentration sensor provided by an embodiment of the present invention;
[0024] Figure 4 The figure is a relationship diagram between the current value output by a glucose concentration sensor and the glucose concentration provided by an embodiment of the present invention.
[0025] Description of reference numerals:
[0026] 10-substrate; 20-two-dimensional electron gas; 30-organic functional group layer; 40-metal electrode layer; 21-gallium nitride layer; 22-aluminum nitride layer; 41-first electrode layer; 42-second electrode layer; 01-first side; 02-second side; 03-third side; 04-fourth side; 05-top surface; 06-polar surface; 07-semi-polar surface. DETAILED DESCRIPTION
[0027] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0028] In the following, in conjunction with the accompanying drawings, a glucose concentration sensor and a preparation method thereof provided in an embodiment of the present application are described in detail through specific embodiments and their application scenarios.
[0029] Reference Figure 1 and Figure 2 , Figure 1 is a schematic diagram of a top view of a glucose concentration sensor according to an embodiment of the present invention, Figure 2 is Figure 1 The schematic diagram of the cross-sectional structure of the glucose concentration sensor along the thickness direction of the glucose concentration sensor at the O-O' line. Figure 1 and Figure 2 As shown, the glucose concentration sensor of the embodiment of the present invention comprises a substrate 10, a gallium nitride layer (GaN) 21, an aluminum nitride layer (AlN) 22, an organic functional group layer 30 and a metal electrode layer 40; the substrate 10 comprises at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced by a first length l 1, and the isosceles trapezoidal structure includes a first side surface 01, a second side surface 02, a third side surface 03, a fourth side surface 04 and a top surface 05. The first side surface 01 and the second side surface 02 are waists of the isosceles trapezoidal structure; the third side surface 03 and the fourth side surface 04 are opposite and perpendicular to the top surface 05. The gallium nitride layer 21 is epitaxial on the first side surface 01 and the second side surface 02, and the aluminum nitride layer 22 is stacked on the upper surface of the gallium nitride layer 21 and the top surface 05 of the isosceles trapezoidal structure. The gallium nitride layer 21 and the aluminum nitride layer 22 stacked on the upper surface of the gallium nitride layer 21 constitute a two-dimensional electron gas (2DEG) 20. The two-dimensional electron gas 20 is used to obtain an electrical signal when the organic functional group layer 30 is combined with the glucose molecule, and the electrical signal is used to indicate the concentration of the glucose molecule. The organic functional group layer 30 is stacked on the upper surface of the aluminum nitride layer 22. The organic functional group layer 30 includes a first region close to the third side surface 03 and a second region close to the fourth side surface 04. The first region and the second region are separated by a second length l. 2 The metal electrode layer 40 includes a first electrode layer 41 and a second electrode layer 42. The first electrode layer 41 is stacked in the first region and extends to the aluminum nitride layer 22 along the plane where the third side 03 is located. The second electrode layer 42 is stacked in the second region and extends to the aluminum nitride layer 22 along the plane where the fourth side 04 is located.
[0030] A two-dimensional electron gas 20, an organic functional group layer 30 and a metal electrode layer 40 are respectively formed on each isosceles trapezoidal structure in the substrate 10. It can be understood that the gaps between adjacent isosceles trapezoidal structures of the substrate 10 are also isosceles trapezoidal structures, and the gaps between adjacent isosceles trapezoidal structures can be called growth grooves for forming the two-dimensional electron gas 20.
[0031] The first length l between adjacent isosceles trapezoidal structures 1 is the length between the adjacent bases of the adjacent isosceles trapezoidal structures, and the third length l between the organic functional group layers 30 on the adjacent isosceles trapezoidal structures 3 is greater than 0, that is, the organic functional group layers on adjacent isosceles trapezoidal structures need to ensure that they do not touch each other. Exemplarily, the first isosceles trapezoidal structure and the second isosceles trapezoidal structure are adjacent isosceles trapezoidal structures in the substrate 10, the first isosceles trapezoidal structure includes a first bottom side and a second bottom side, the second isosceles trapezoidal structure includes a third bottom side and a fourth bottom side, and the second bottom side of the first isosceles trapezoidal structure is adjacent to the third bottom side of the second isosceles trapezoidal structure, then the first length l between the first isosceles trapezoidal structure and the second isosceles trapezoidal structure is spaced 1 is the distance between the second base and the third base. It should be noted that the base of the isosceles trapezoidal structure is the base corresponding to the waist of the isosceles trapezoidal structure.
[0032] It can be understood that each isosceles trapezoidal structure includes four side faces and a top face 05, the first side face 01 is opposite to the second side face 02, and is the waist of the isosceles trapezoidal structure, the third side face 03 is opposite to the fourth side face 04, and is the side faces other than the waist of the isosceles trapezoidal structure, and in the embodiment of the present invention, the third side face 03 and the fourth side face 04 are both perpendicular to the top face 05 of the isosceles trapezoidal structure.
[0033] In the organic functional group layer 30, the first region is a region of the organic functional group layer 30 extending from the edge close to the third side 03 to the center of the organic functional group layer 30, and the second region is a region of the organic functional group layer 30 extending from the edge close to the fourth side 04 to the center of the organic functional group layer 30. The first region and the second region are separated by a second length l 2 , the second length l 2 Greater than 0, that is, the first region and the second region need to ensure that they do not contact each other, so as to avoid the first electrode layer 41 stacked in the first region and the second electrode layer 42 stacked in the second region from contacting each other to cause a short circuit. The first width of the first region along the direction from the edge of the organic functional group layer close to the third side to the center of the organic functional group layer is 5 μm to 500 μm, and the second width of the second region along the direction from the edge of the organic functional group layer close to the fourth side to the center of the organic functional group layer is the same as the first width, also 5 μm to 500 μm.
[0034] In the embodiment of the present invention, the two-dimensional electron gas 20 covers the first side surface 01 and the second side surface 02 of the isosceles trapezoidal structure, and the organic functional group layer 03 is stacked on the entire upper surface of the two-dimensional electron gas 20, and the metal electrode layer 40 is only stacked on the first area close to the third side surface 03 and the second area close to the fourth side surface 04 of the organic functional group layer 30, so that the glucose concentration sensor can realize electrical signal transmission through the metal electrode layer 40 while ensuring sufficient contact between the surface of the organic functional group layer 30 and the glucose molecules, and determine the concentration of the glucose molecules based on the electrical signal obtained by the two-dimensional electron gas 20 when the organic functional group layer 30 combines with the glucose molecules.
[0035] Specifically, when the glucose molecules and the organic functional group layer 30 specifically combine to form an electrical signal, the two-dimensional electron gas 20 acquires the electrical signal and transmits the electrical signal to an electrical signal receiving device connected to the glucose concentration sensor through the metal electrode layer 40. The user can view the electrical signal from the electrical signal receiving device and determine the specific concentration of the glucose molecules based on the electrical signal.
[0036] Among them, the two-dimensional electron gas 20 is a system that uses physical methods such as quantum confinement to limit the movement of electron groups in one direction (such as the z direction) to a very small range, while the system can move freely in the other two directions (such as the x direction and the y direction) is called a two-dimensional electron system. If the electron density in the two-dimensional electron system is high, it is called a two-dimensional electron gas 20.
[0037] In the embodiment of the present invention, the material of the two-dimensional electron gas 20 may include but is not limited to aluminum nitride / gallium nitride, aluminum gallium nitride (AlGaN) / gallium nitride, and the like.
[0038] The glucose molecules may be glucose molecules in any liquid, for example, the glucose molecules may be glucose molecules in blood or glucose molecules in a glucose solution. The electrical signal may be a current value or a voltage value.
[0039] In the embodiment of the present invention, when the resistance of the glucose concentration sensor is constant, the concentration of glucose molecules is positively correlated with the current value, and the concentration of glucose molecules is positively correlated with the voltage value.
[0040] Before using the glucose concentration sensor to detect the concentration of glucose molecules, the glucose concentration sensor can be used to measure multiple groups of target liquids with known glucose molecule concentrations to determine the correlation between the concentration of glucose molecules and electrical signals; in the process of using the glucose concentration sensor to detect the concentration of glucose molecules, the concentration of glucose molecules can be determined based on the predetermined correlation and the electrical signals obtained by the two-dimensional electron gas 20.
[0041] In the embodiment of the present invention, the two-dimensional electron gas 20 is obtained by combining gallium nitride and aluminum nitride, and the aluminum nitride layer 22 is coated on the upper surface of the gallium nitride layer 21, and the two-dimensional electron gas 20 is formed at the interface between the aluminum nitride layer 22 and the gallium nitride layer 21. The glucose concentration sensor provided by the embodiment of the present invention uses the two-dimensional electron gas 20 formed by the heterojunction interface of the gallium nitride layer 21 and the aluminum nitride layer 22 to capture the electrical signal when the organic functional group layer 30 and the glucose molecule are specifically combined, so as to achieve the purpose of detecting the concentration of glucose molecules, and the gallium nitride grown by this method has low stress and high crystal quality, which reduces the scattering effect of defects in the first side surface 01 and the second side surface 02 on the two-dimensional electron gas 20, improves the mobility of the two-dimensional electron gas 20, and thus improves the accuracy and sensitivity of the glucose concentration sensor in detecting the concentration of glucose molecules.
[0042] The substrate 10 is a silicon (Si) substrate, and the first side surface 01 and the second side surface 02 are 111 crystal planes of the Si substrate. The metal electrode layer 40 may include one or more of titanium (Ti), aluminum (Al), nickel (Ni), gold (Au), platinum (Pt), molybdenum (Mo), iridium (Ir), tantalum (Ta), niobium (Nb), cobalt (Co), and tungsten (W).
[0043] Based on the problems of high testing cost, complicated testing process and low sensitivity in the existing glucose concentration detection methods, the glucose concentration sensor provided in the embodiment of the present invention includes a substrate 10, a gallium nitride layer 21, an aluminum nitride layer 22, an organic functional group layer 30 and a metal electrode layer 40; wherein the substrate 10 includes at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced apart by a first length, and the two-dimensional electron gas 20 and the organic functional group layer 30 stacked in sequence on each isosceles trapezoidal structure have a large specific surface area, which increases the contact probability between the glucose molecules and the organic functional group layer 30, and improves the detection efficiency of the glucose concentration sensor; the gallium nitride layer 21 is epitaxial on the first side surface 01 and the second side surface 02 of the isosceles trapezoidal structure, and the aluminum nitride layer 22 is stacked on the upper surface of the gallium nitride layer 21 and the top surface 05 of the isosceles trapezoidal structure, so that the gallium nitride layer 21 and the aluminum nitride layer 22 stacked on the upper surface of the gallium nitride layer 21 constitute a two-dimensional electron gas. 20, the organic functional group layer 30 is stacked on the upper surface of the aluminum nitride layer 22, the first electrode layer 41 of the metal electrode layer 40 is stacked on the first region of the organic functional group layer 30, and extends to the aluminum nitride layer 22 along the plane where the third side 03 of the isosceles trapezoidal structure is located, and the second electrode layer 42 of the metal electrode layer 40 is stacked on the second region, and extends to the aluminum nitride layer 22 along the plane where the fourth side 04 is located; the electron concentration of the two-dimensional electron gas layer 20 is sensitive to weak electrical signals, and the weak electrical signals before and after the specific binding of the organic functional group layer 30 and the glucose molecule can be obtained in real time, and the electrical signals are output through the metal electrode layer 40, thereby reducing the detection limit of the glucose concentration and improving the sensitivity of the glucose concentration sensor; further, the organic functional group layer 30 is directly stacked on the surface of the two-dimensional electron gas 20, which can shorten the distance between the organic functional group layer 30 and the two-dimensional electron gas 20, and further improve the sensitivity of the glucose concentration sensor. Using the glucose concentration sensor provided in the embodiment of the present invention to detect glucose concentration not only improves the detection sensitivity and detection efficiency of glucose concentration, but also facilitates operation and reduces the detection cost of glucose concentration.
[0044] Optionally, refer to Figure 1 The gallium nitride layer 21 includes a polar surface 06 and a semi-polar surface 07 ; wherein the polar surface 06 is a surface parallel to the first side surface 01 or the second side surface 02 , and the semi-polar surface 07 is a surface other than the polar surface 06 in the gallium nitride layer 21 .
[0045] In the glucose concentration sensor provided by the embodiment of the present invention, the gallium nitride layer 21 has a polar surface 06 and two semi-polar surfaces 07. Compared with the first direction perpendicular to the semi-polar surface 07, the gallium nitride layer 21 grows faster in the second direction perpendicular to the polar surface 06. During the growth of the gallium nitride layer 21, the stress can be well released, so that there are fewer defects at the heterojunction interface between the gallium nitride layer 21 and the aluminum nitride layer 22, and the crystal quality is higher. The mobility of the two-dimensional electron gas 20 formed by the heterojunction interface between the gallium nitride layer 21 and the aluminum nitride layer 22 can be greatly improved, so that the glucose concentration sensor is more sensitive in the process of detecting the concentration of glucose molecules.
[0046] It can be understood that, when the growth rate of the gallium nitride layer 21 in the second direction perpendicular to the polar surface 06 is greater than the growth rate in the first direction perpendicular to the semi-polar surface 07, the cross-sectional shape of the gallium nitride layer 21 epitaxially grown on the first side surface 01 and the second side surface 02 along the thickness direction of the glucose concentration sensor is: Figure 1 The isosceles trapezoid shown.
[0047] Optionally, in some embodiments, the thickness of the gallium nitride layer 21 is 1 μm to 10 μm. For example, the thickness of the gallium nitride layer 21 can be one or any two of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm.
[0048] The thickness of the gallium nitride layer 21 is the distance from a surface of the gallium nitride layer 21 parallel to the first side surface 01 (ie, the polar surface 06 ) to the first side surface 01 .
[0049] Optionally, in some embodiments, the thickness of the aluminum nitride layer 22 is 15nm to 30nm. For example, the thickness of the aluminum nitride layer 22 can be a range of one or any two of 15nm, 18nm, 20nm, 22nm, 24nm, 26nm, 28nm, 30nm, 32nm and 35nm.
[0050] The thickness of the aluminum nitride layer 22 is the distance between the surface of the aluminum nitride layer 22 stacked with the gallium nitride layer 21 and the surface of the aluminum nitride layer 22 stacked with the organic functional group layer 30 .
[0051] Optionally, in some embodiments, the organic functional group layer 30 is any one of a glucose carbon quantum dot chitosan molecular imprinted film, a boric acid functionalized carbon quantum dot molecular imprinted film and a reduced graphene-nano copper molecular imprinted film.
[0052] Optionally, in some embodiments, the height of each isosceles trapezoidal structure in the substrate 10 is 1 μm to 5 μm, for example, it can be one or any two of 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm.
[0053] The height of the isosceles trapezoidal structure refers to the distance between the plane formed by the bottom sides of each isosceles trapezoidal structure and the top surface 05 of the isosceles trapezoidal structure.
[0054] It should be noted that, in the embodiment of the present invention, the heights of the isosceles trapezoidal structures in the substrate 10 are equal.
[0055] Optionally, in some embodiments, the thickness of the substrate 10 is 2 μm to 200 μm; for example, the thickness of the substrate 10 can be a range of one or any two of 1 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm and 200 μm.
[0056] The thickness of the substrate 10 is the distance between the bottom surface of the substrate 10 and the top surface 05 of the isosceles trapezoidal structure.
[0057] Optionally, in some embodiments, the thickness of the organic functional group layer 30 is 200nm to 1000nm; for example, the thickness of the organic functional group layer 30 can be a range of one or any two of 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm and 1000nm.
[0058] Optionally, in some embodiments, the thickness of the metal electrode layer 40 is 50nm to 1000nm; for example, the thickness of the metal electrode layer 40 can be a range of one or any two of 50nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm and 1000nm.
[0059] It can be understood that the thicknesses of the first electrode layer 41 and the second electrode layer 42 in the metal electrode layer 40 are equal, and the thicknesses of the first electrode layer 41 and the second electrode layer 42 are both 50 nm to 1000 nm.
[0060] The embodiment of the present invention also provides a method for preparing any of the aforementioned glucose concentration sensors. Figure 3 , shows a flowchart of a method for preparing a glucose concentration sensor according to an embodiment of the present invention, the method comprising steps S101 to S105:
[0061] Step S101, obtaining a substrate.
[0062] Wherein, the substrate includes at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced by a first length; the isosceles trapezoidal structure includes a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are the waists of the isosceles trapezoidal structure; the third side surface and the fourth side surface are opposite to each other and are perpendicular to the top surface.
[0063] In this step, the substrate is a silicon substrate, and at least one isosceles trapezoidal structure is pre-prepared on the substrate to meet the needs of preparing a gallium nitride layer in the subsequent step S102, preparing an aluminum nitride layer in step S103, preparing an organic functional group layer in step S104, and preparing a metal electrode layer in step S105.
[0064] The thickness of the substrate may be 1 μm to 200 μm; the height of the mid-waist trapezoidal structure in the substrate may be 1 μm to 5 μm.
[0065] Step S102 , epitaxially growing a gallium nitride layer on the first side surface and the second side surface.
[0066] Step S103 , growing an aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure.
[0067] The gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas; the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined; the electrical signal is used to indicate the concentration of the glucose molecule. The material of the two-dimensional electron gas 20 may include but is not limited to aluminum nitride / gallium nitride, aluminum gallium nitride / gallium nitride, etc.
[0068] In an embodiment of the present invention, the two-dimensional electron gas is formed by the heterojunction interface of the gallium nitride layer and the aluminum nitride layer; in the process of preparing the two-dimensional electron gas, the gallium nitride layer can be grown on the first side and the second side of the isosceles trapezoidal structure by using the selective epitaxial growth technology through step S102, and then the aluminum nitride layer is grown on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure through step S103, so as to form the two-dimensional electron gas at the heterojunction interface of the gallium nitride layer and the aluminum nitride layer.
[0069] Trimethylgallium (Ga(CH 3 ) 3 ) as a precursor of gallium, trimethylaluminium (Trimethylaluminium, C 3 H 9 Al) as a precursor of aluminum and ammonia (NH 3) as a nitrogen precursor. Specifically, before step S102, the substrate obtained in step S101 can be loaded into a metal-organic chemical vapor deposition (MOCVD) reactor; in step S102, the gasification gas of trimethylgallium and ammonia is introduced into the MOCVD reactor to selectively grow a gallium nitride layer on the first side and the second side of the isosceles trapezoidal structure; in step S103, the gasification gas of trimethylaluminum and ammonia is introduced into the MOCVD reactor to grow an aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure.
[0070] It can be understood that the first side and the second side of the isosceles trapezoidal structure are the same crystal planes, while the third side and the fourth side of the isosceles trapezoidal structure are different from the first side and the second side. The crystal planes corresponding to the first side and the second side are crystal planes that are conducive to the growth of gallium nitride. Therefore, in step S102, the gallium nitride layer will preferentially grow on the first side and the second side, and in the process of the gallium nitride layer preferentially growing on the first side and the second side, the stress can be well released. Compared with conventional thin film structures, the heterojunction structure interface crystal prepared by this method has higher quality and fewer defects, which can improve the mobility of the two-dimensional electron gas, so that the prepared glucose concentration sensor is more sensitive to the detection of glucose molecule concentration.
[0071] The gallium nitride layer includes a polar surface and a semi-polar surface; the polar surface is a surface parallel to the first side surface or the second side surface, and the semi-polar surface is a surface other than the polar surface in the gallium nitride layer. In the two-dimensional electron gas, the thickness of the gallium nitride layer is 1 μm to 10 μm, and the thickness of the aluminum nitride layer is 15 nm to 30 nm.
[0072] Step S104, spin-coating a first solution on the upper surface of the aluminum nitride layer, and drying the first solution spin-coated on the aluminum nitride layer to obtain an organic functional group layer; the organic functional group layer includes a first area close to the third side and a second area close to the fourth side, and the first area and the second area are spaced apart by a second length.
[0073] Specifically, in the organic functional group layer, the first region is a region of the organic functional group layer extending from an edge close to the third side to the center of the organic functional group layer, and the second region is a region of the organic functional group layer extending from an edge close to the fourth side to the center of the organic functional group layer. The first region and the second region are separated by a second length, and the second length is greater than 0, that is, the first region and the second region need to ensure that they do not contact each other, so as to avoid the first electrode layer deposited in the first region and the second electrode layer deposited in the second region contacting each other in step S104 to cause a short circuit.
[0074] The first solution is a precursor solution corresponding to a pre-prepared organic functional group layer; the thickness of the organic functional group is 200nm to 1000nm.
[0075] In the embodiment of the present invention, the organic functional group layer is any one of a glucose carbon quantum dot chitosan molecular imprinted film, a boric acid functionalized carbon quantum dot molecular imprinted film and a reduced graphene-nano copper molecular imprinted film.
[0076] Specifically, when the organic functional group layer is a glucose carbon quantum dot chitosan molecular imprinted film, the first solution is an ethanol solution of glucose carbon quantum dot chitosan molecular imprinted polymer. When the first solution is an ethanol solution of glucose carbon quantum dot chitosan molecular imprinted polymer, the preparation method of the first solution includes the following steps A11 to A14:
[0077] Step A11: synthesize carbon quantum dot (CDs) nanomaterials using a carbon source as a material, and mix the carbon quantum dot nanomaterials with a chitosan (CS) solution having good film-forming properties in a first ratio to obtain a first solution.
[0078] Among them, the first ratio is 1:7 to 1:3.
[0079] Step A12: modify the first solution onto the surface of the glassy carbon electrode (GCE), and place the glassy carbon electrode in an oven for drying to obtain CDs-CS / GCE.
[0080] The drying temperature is 10°C to 100°C, and the drying time is 10 min to 60 min.
[0081] Step A13, using 3-aminophenylboronic acid (APBA) as a functional monomer and glucose as a template molecule, a three-electrode system was used to synthesize glucose carbon quantum dot chitosan molecularly imprinted polymer (MIP) on CDs-CS / GCE.
[0082] Specifically, first, 3-aminophenylboronic acid and glucose are mixed in equal proportions (the ratio ranges from 0.8:1 to 1.2:1) to obtain a second solution; then, the second solution is coated on CDs-CS / GCE; finally, a voltage of 1V to 10V is applied to the CDs-CS / GCE coated with the second solution using any three of the four electrodes of gold / platinum / silver / copper for 1min to 10min to obtain glucose carbon quantum dot chitosan molecular imprinting polymer.
[0083] Step A14, ultrasonically cleaning the glucose carbon quantum dot chitosan molecular imprinted polymer in an ethanol solution to obtain a glucose carbon quantum dot chitosan molecular imprinted film.
[0084] Among them, the duration of ultrasonic cleaning is 5min to 30min.
[0085] In the case where the organic functional group layer is a boric acid functionalized carbon quantum dot molecular imprinting film, the first solution is an ethanol solution of a boric acid functionalized carbon quantum dot molecular imprinting polymer. In the case where the first solution is an ethanol solution of a boric acid functionalized carbon quantum dot molecular imprinting polymer, the method for preparing the first solution includes the following steps A21 to A26:
[0086] Step A21: Sodium citrate (Na 3 C 6 H 5 O 7 ·2H 2 O) and aminophenylboronic acid (PBA) as precursors were dissolved in 40 mL of distilled water to obtain a third solution.
[0087] Wherein, the mass ratio of sodium citrate to aminophenylboronic acid is 1.2:1 to 2:1.
[0088] Step A22, adjusting the pH of the third solution to neutral, and continuously introducing nitrogen into the third solution with a neutral pH value to remove dissolved oxygen in the third solution.
[0089] The pH of the third solution is adjusted to neutral by adding sodium hydroxide (NaOH) and / or potassium hydroxide (KOH) to the third solution. The flow rate of the nitrogen gas is in the range of 10 sccm to 200 sccm, and the duration of the nitrogen gas is in the range of 1 min to 30 min.
[0090] Step A23, heating the third solution in a reaction vessel, and cooling the third solution to room temperature after the heating.
[0091] The temperature of the heating treatment is 100° C. to 300° C., and the duration of the heating treatment is 1 hour to 12 hours.
[0092] Step A24, centrifuging the third solution cooled to room temperature, and freeze-drying the third solution after the centrifugation to obtain solid boric acid functionalized carbon quantum dots (APBA-CDs).
[0093] The purpose of centrifuging the third solution cooled to room temperature is to remove the precipitate in the third solution.
[0094] The rotation speed of the centrifugal operation is 500 rpm / min to 3000 rpm / min, and the duration of the centrifugal operation is 1 min to 30 min.
[0095] Step A25: using APBA-CDs as a carrier, obtaining a boric acid functionalized carbon quantum dot molecular imprinting polymer by sol-gel polymerization under the action of methyl orthosilicate (TMOS) and phenyltriethoxysilane (TEOS).
[0096] Specifically, first, APBA-CDs, methyl orthosilicate and phenyltriethoxysilane are mixed in a second ratio to obtain a fourth solution; then, the fourth solution is heat-insulated using a muffle furnace to obtain a first mixture; finally, the first mixture is allowed to stand at room temperature for 24 to 48 hours to obtain a boric acid functionalized carbon quantum dot molecular imprinting polymer.
[0097] Among them, the second ratio is 1.5:1:1 to 2:1:1; the temperature of the insulation treatment is 10°C to 300°C, and the duration of the insulation treatment is 1 hour to 10 hours.
[0098] Step A26, ultrasonically cleaning the boric acid functionalized carbon quantum dot molecular imprinting polymer in an ethanol solution to obtain a boric acid functionalized carbon quantum dot molecular imprinting film.
[0099] Among them, the duration of ultrasonic cleaning is 5min to 30min.
[0100] In the case where the organic functional group layer is a reduced graphene-nano copper molecular imprinted film, the first solution is an ethanol solution of reduced graphene-nano copper molecular imprinted polymer. In the case where the first solution is an ethanol solution of reduced graphene-nano copper molecular imprinted polymer, the preparation method of the first solution includes the following steps A31 to A35:
[0101] Step A31, dispersing graphene oxide (GO) in N,N-dimethylformamide (DMF) and performing ultrasonic treatment to obtain a dispersion.
[0102] The mass ratio of graphene oxide to N,N-dimethylformamide is 1:3 to 1:8; and the duration of ultrasonic treatment is 10 min to 60 min.
[0103] Step A32: Apply the dispersed droplets on the surface of the glassy carbon electrode and dry it at room temperature to obtain a graphene oxide modified electrode (GO-GCE).
[0104] The dispersion liquid is dripped with a thickness of 1 mm to 200 mm.
[0105] Step A33, treating GO-GCE in a mixed solution of copper sulfate and sodium citrate to obtain rGO-CuNPs-GCE.
[0106] Step A34: using glucose as a template molecule and p-aminobenzoic acid as a functional monomer, rGO-CuNPs-GCE is prepared by electropolymerization to obtain reduced graphene-nano copper molecular imprinting polymer.
[0107] Specifically, first, glucose and p-aminobenzoic acid are mixed in a third ratio to obtain a fifth solution; then, the fifth solution is heat-insulated in a muffle furnace to obtain a second mixture, and the second mixture is naturally cooled to room temperature; then, the second mixture cooled to room temperature is added to rGO-CuNPs-GCE, and any one of gold / platinum / silver / copper is used as an electrode, and a voltage of 1V to 10V is applied to the rGO-CuNPs-GCE to which the second mixture is added, and the voltage is continued for 1min to 10min to obtain a reduced graphene-nanocopper molecular imprinting polymer.
[0108] Among them, the third ratio is 0.8:1 to 1.2:1; the temperature of the insulation treatment is 10°C to 200°C, and the duration of the insulation treatment is 1 hour to 10 hours.
[0109] Step A35, ultrasonically cleaning the reduced graphene-nano copper molecularly imprinted polymer in an ethanol solution to obtain a reduced graphene-nano copper molecularly imprinted film.
[0110] Among them, the duration of ultrasonic cleaning is 5min to 30min.
[0111] Step S105, depositing a first electrode layer in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the first area and the third side are located, and depositing a second electrode layer in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the second area and the fourth side are located, to obtain a glucose concentration sensor.
[0112] Among them, the first electrode layer and the second electrode layer constitute the metal electrode layer of the glucose concentration sensor; the thickness of the metal electrode layer is 50nm to 1000nm; it can be understood that the thickness of the first electrode layer and the second electrode layer in the metal electrode layer are equal, and the thickness of the first electrode layer and the second electrode layer are both 50nm to 1000nm; exemplarily, when the first electrode layer is the positive electrode of the glucose concentration sensor, the second electrode layer is the negative electrode of the glucose concentration sensor; when the first electrode layer is the negative electrode of the glucose concentration sensor, the second electrode layer is the positive electrode of the glucose concentration sensor.
[0113] In this step, the first electrode layer and the second electrode layer may be deposited by electroplating electrophoresis, molecular deposition, atomic deposition, etc. to obtain a glucose concentration sensor.
[0114] The first electrode layer and the second electrode layer are used to transmit the electrical signal acquired by the two-dimensional electron gas to an electrical signal receiving device connected to the glucose concentration sensor, so that the user can view and analyze the electrical signal from the electrical signal receiving device.
[0115] Specifically, when the glucose molecules and the organic functional group layer specifically combine to form an electrical signal, the two-dimensional electron gas acquires the electrical signal and transmits the electrical signal to an electrical signal receiving device connected to the glucose concentration sensor through the first electrode layer and the second electrode layer. The user can view the electrical signal from the electrical signal receiving device and determine the concentration of the glucose molecules based on the electrical signal.
[0116] The preparation method of the glucose concentration sensor provided by the embodiment of the present invention is based on a substrate including at least one isosceles trapezoidal structure, and the two-dimensional electron gas and the organic functional group layer prepared in sequence on the isosceles trapezoidal structure of the substrate have a large specific surface area, which increases the contact probability between the glucose molecules and the organic functional group layer, and improves the detection efficiency of the glucose concentration sensor; a gallium nitride layer is epitaxially grown on the first side surface and the second side surface of the isosceles trapezoidal structure, and an aluminum nitride layer is grown on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure, so that the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas, and an organic functional group layer is prepared on the upper surface of the aluminum nitride layer, so that the organic functional group layer is stacked on the upper surface of the aluminum nitride layer, and in the first area and the second area The first electrode layer is deposited in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the three side surfaces are located, and the second electrode layer is deposited in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the second region and the fourth side surfaces are located, to obtain a glucose concentration sensor, the electron concentration of the two-dimensional electron gas layer is sensitive to weak electrical signals, and the weak electrical signals before and after the specific binding of the organic functional group layer and the glucose molecule can be obtained in real time, and the electrical signals are output through the metal electrode layer, thereby reducing the detection limit of the glucose concentration and improving the sensitivity of the glucose concentration sensor; further, the organic functional group layer is directly stacked on the surface of the two-dimensional electron gas, which can shorten the distance between the organic functional group layer and the two-dimensional electron gas, further improving the sensitivity of the glucose concentration sensor. The glucose concentration sensor prepared by the preparation method of the glucose concentration sensor provided by the embodiment of the present invention not only improves the detection sensitivity and detection efficiency of the glucose concentration, but also is easy to operate and reduces the detection cost of the glucose concentration.
[0117] Optionally, in some embodiments, the temperature for epitaxially growing the gallium nitride layer on the first side and the second side is 1000°C to 1050°C; for example, the temperature for epitaxially growing gallium nitride can be in the range of one or any two of 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C.
[0118] Optionally, in some embodiments, the pressure for epitaxially growing the gallium nitride layer on the first side and the second side is 100 mbar to 500 mbar; for example, the pressure for epitaxially growing gallium nitride can be in the range of one or any two of 100 mbar, 200 mbar, 300 mbar, 400 mbar, 500 mbar.
[0119] Optionally, in some embodiments, the time for epitaxially growing the gallium nitride layer on the first side and the second side is 100s to 1000s; for example, the time for epitaxially growing gallium nitride can be a range value of one or any two of 100s, 200s, 300s, 400s, 500s, 600s, 700s, 800s, 900s, 1000s.
[0120] Optionally, in some embodiments, the temperature for growing the aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure is 1000°C to 1050°C; for example, the temperature for growing the aluminum nitride layer can be a range of one or any two of 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C.
[0121] Optionally, in some embodiments, the pressure for growing the aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure is 10 mbar to 200 mbar; for example, the pressure for growing the aluminum nitride layer can be a range of one or any two of 10 mbar, 20 mbar, 40 mbar, 60 mbar, 80 mbar, 100 mbar, 120 mbar, 140 mbar, 160 mbar, 180 mbar, and 200 mbar.
[0122] Optionally, in some embodiments, the time for growing the aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure is 10s to 100s; for example, the time for growing the aluminum nitride layer can be a range of one or any two of 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, and 100s.
[0123] Optionally, in some embodiments, the step S101 of obtaining a substrate includes steps S1011 to S1012:
[0124] Step S1011: Under a constant temperature condition, anisotropically etch any surface of the original substrate using an alkaline solution to obtain an original substrate including at least one isosceles trapezoidal structure.
[0125] Among them, the temperature of the constant temperature condition is 10°C to 60°C, for example, it can be one of 10°C, 20°C, 30°C, 40°C, 50°C, 60°C or any two of the range values; the duration of the anisotropic etching treatment is 10min to 30min, for example, it can be one of 10min, 15min, 20min, 25min, 30min or any two of the range values; the concentration of the alkaline solution is 20wt.% to 50wt.%, for example, it can be one of 20wt.%, 30wt.%, 40wt.%, 50wt.% or any two of the range values.
[0126] In this step, the alkaline solution may include but is not limited to potassium hydroxide solution and sodium hydroxide solution.
[0127] Step S1012: Clean the original substrate including at least one isosceles trapezoidal structure using a hydrofluoric acid solution to obtain a substrate.
[0128] Among them, the concentration of the hydrofluoric acid solution is 10wt.% to 30wt.%, for example, it can be one of 10wt.%, 15wt.%, 20wt.%, 25wt.%, 30wt.% or any two of the range values; the cleaning time is 1min to 10min, for example, it can be one of 1min, 2min, 3min, 4min, 5min, 6min, 7min, 8min, 9min, 10min or any two of the range values.
[0129] In an embodiment of the present invention, a hydrogen-passivated surface without oxides is obtained in the substrate by cleaning an original substrate including at least one isosceles trapezoidal structure with a hydrofluoric acid solution. A glucose concentration sensor is prepared based on a substrate having a hydrogen-passivated surface without oxides, and the crystal defect concentration in each functional layer in the glucose concentration sensor can be reduced, thereby improving the crystal quality.
[0130] Optionally, in some embodiments, the step S104 includes depositing a first electrode layer in a region corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the first region and the third side are located, and depositing a second electrode layer in a region corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the second region and the fourth side are located, to obtain a glucose concentration sensor, comprising steps S1041 to S1043:
[0131] Step S1041 , depositing a first electrode layer in a region corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the first region of the organic functional group layer and the third side face are located by electron beam evaporation of a target metal.
[0132] Step S1042: Depositing a second electrode layer in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the second region of the organic functional group layer and the fourth side face are located by electron beam evaporation of the target metal.
[0133] Step S1043: annealing the first electrode layer and the second electrode layer to obtain a glucose concentration sensor.
[0134] Among them, the environment of the annealing treatment is a nitrogen environment; the temperature of the annealing treatment is 500°C to 1000°C, for example, it can be one of 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C or any two of the range values; the duration of the annealing treatment is 10s to 100s, for example, it can be one of 10s, 20s, 30s, 40s, 50s, 60s, 70s, 80s, 90s, 100s or any two of the range values.
[0135] The target metal may be one or more of titanium, aluminum, nickel, gold, platinum, molybdenum, iridium, tantalum, niobium, cobalt, and tungsten.
[0136] Exemplarily, when the target metal is titanium, aluminum, nickel, and gold, in step S1041, a titanium layer, an aluminum layer, a nickel layer, and a gold layer may be deposited in sequence in the first region and in the plane where the third side is located in the region corresponding to the organic functional group layer and the aluminum nitride layer to obtain a first electrode layer including a titanium layer, an aluminum layer, a nickel layer, and a gold layer stacked in sequence. The thickness of the titanium layer is 10nm to 30nm, the thickness of the aluminum layer is 100nm to 300nm, the thickness of the nickel layer is 10nm to 30nm, and the thickness of the gold layer is 10nm to 100nm. It should be noted that when the first electrode layer includes at least one metal layer, the sum of the thicknesses of the metal layers is 50nm to 1000nm.
[0137] In the case where the target metal is titanium, aluminum, nickel, and gold, in step S1042, a titanium layer, an aluminum layer, a nickel layer, and a gold layer may be deposited in sequence in the region corresponding to the organic functional group layer and the aluminum nitride layer in the second region and the plane where the fourth side is located, to obtain a second electrode layer including a titanium layer, an aluminum layer, a nickel layer, and a gold layer stacked in sequence. The thickness of the titanium layer is 10nm to 30nm, the thickness of the aluminum layer is 100nm to 300nm, the thickness of the nickel layer is 10nm to 30nm, and the thickness of the gold layer is 10nm to 100nm. It should be noted that in the case where the second electrode layer includes at least one metal layer, the sum of the thicknesses of the metal layers is 50nm to 1000nm.
[0138] In order to make the invention purpose, technical scheme and beneficial effect of the present invention clearer, the present invention is further described below in conjunction with embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0139] The present invention is described in detail below by way of examples.
[0140] Example 1
[0141] (1) Obtaining a substrate:
[0142] First, an anisotropic etching treatment is performed on the surface of an original silicon substrate using an alkaline solution under a constant temperature condition to obtain an original silicon substrate including at least one isosceles trapezoidal structure; then, the original silicon substrate including at least one isosceles trapezoidal structure is cleaned using a hydrofluoric acid solution to obtain a silicon substrate;
[0143] Among them, the temperature of the constant temperature condition is 40°C, the duration of the anisotropic etching treatment is 18 minutes, the concentration of the alkaline solution is 40wt.%; the concentration of the hydrofluoric acid solution is 20wt.%, and the cleaning time is 5 minutes; the silicon substrate includes four isosceles trapezoidal structures, and the interval between adjacent isosceles trapezoidal structures is 20μm; the isosceles trapezoidal structure includes a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are the waists of the isosceles trapezoidal structure; the third side surface and the fourth side surface are opposite and perpendicular to the top surface; the height of the isosceles trapezoidal structure is 3μm, and the thickness of the silicon substrate is 100μm.
[0144] (2) Preparation of two-dimensional electron gas:
[0145] First, a silicon substrate is loaded into an MOCVD reactor; then, gasified gas of trimethylgallium and ammonia is introduced into the MOCVD reactor to epitaxially grow a gallium nitride layer on a first side surface and a second side surface of an isosceles trapezoidal structure of the silicon substrate; then, gasified gas of trimethylaluminum and ammonia is introduced into the MOCVD reactor to grow an aluminum nitride layer on an upper surface of the gallium nitride layer and a top surface of the isosceles trapezoidal structure, and the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer form a two-dimensional electron gas; the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined, and the electrical signal is used to indicate the concentration of the glucose molecule;
[0146] Among them, the thickness of the gallium nitride layer is 5μm, and the thickness of the aluminum nitride layer is 20nm; the gallium nitride layer includes a polar surface and a semi-polar surface, and the polar surface is a surface parallel to the first side or the second side, and the semi-polar surface is a surface other than the polar surface in the gallium nitride layer; the temperature for epitaxial growth of the gallium nitride layer is 1020°C, the pressure for epitaxial growth of the gallium nitride layer is 400mbar, and the time for epitaxial growth of the gallium nitride layer is 800s; the temperature for growing the aluminum nitride layer is 1050°C, the pressure for growing the aluminum nitride layer is 75mbar, and the time for growing the aluminum nitride layer is 90s.
[0147] (3) Preparation of organic functional group layer:
[0148] A first solution is spin-coated on the upper surface of the aluminum nitride layer, and the first solution spin-coated on the aluminum nitride layer is dried to obtain an organic functional group layer; wherein the organic functional group layer includes a first region close to the third side and a second region close to the fourth side, the first region and the second region are spaced 10 μm apart, a first width of the first region from an edge of the organic functional group layer close to the third side to a center of the organic functional group layer is 100 μm, and a second width of the second region from an edge of the organic functional group layer close to the fourth side to a center of the organic functional group layer is 100 μm; the first solution is an ethanol solution of a glucose carbon quantum dot chitosan molecular imprinting polymer, and the organic functional group layer is a glucose carbon quantum dot chitosan molecular imprinting film; the thickness of the organic functional group layer is 500 nm.
[0149] (4) Preparation of glucose concentration sensor:
[0150] First, a first electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where a first area and a third side of the organic functional group layer are located by electron beam evaporation, and a second electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where a second area and a fourth side of the organic functional group layer are located; then, the first electrode layer and the second electrode layer are annealed to obtain a glucose concentration sensor, wherein the first electrode layer and the second electrode layer constitute a metal electrode layer of the glucose concentration sensor; wherein the target metal comprises titanium, aluminum, nickel and gold; the metal electrode layer comprises a titanium layer, an aluminum layer, a nickel layer and a gold layer stacked in sequence, wherein the thickness of the titanium layer is 25 nm, the thickness of the aluminum layer is 150 nm, the thickness of the nickel layer is 25 nm, and the thickness of the gold layer is 50 nm; the annealing environment is a nitrogen environment, the annealing temperature is 800°C, and the annealing time is 30 s.
[0151] Example 2
[0152] The difference between Example 2 and Example 1 is that in step (1), the temperature of the constant temperature condition is 10° C., the duration of the anisotropic etching treatment is 30 min, and the concentration of the alkaline solution is 50 wt.%.
[0153] Example 3
[0154] The difference between Example 3 and Example 1 is that in step (1), the temperature of the constant temperature condition is 60° C., the duration of the anisotropic etching treatment is 10 min, and the concentration of the alkaline solution is 20 wt.%.
[0155] Example 4
[0156] The difference between Example 4 and Example 1 is that in step (1), the concentration of the hydrofluoric acid solution is 10 wt.%, and the cleaning time is 10 min.
[0157] Example 5
[0158] The difference between Example 5 and Example 1 is that in step (1), the concentration of the hydrofluoric acid solution is 30 wt.%, and the cleaning time is 1 min.
[0159] Example 6
[0160] The difference between Example 6 and Example 1 is that in step (1), the height of the isosceles trapezoidal structure is 1 μm, and the thickness of the silicon substrate is 2 μm.
[0161] Example 7
[0162] The difference between Example 7 and Example 1 is that in step (1), the height of the isosceles trapezoidal structure is 5 μm, and the thickness of the silicon substrate is 200 μm.
[0163] Example 8
[0164] The difference between Example 8 and Example 1 is that in step (2), the thickness of the gallium nitride layer is 1 μm; the temperature for growing the gallium nitride layer is 1000° C., the pressure for growing the gallium nitride layer is 100 mbar, and the time for growing the gallium nitride layer is 100 s.
[0165] Example 9
[0166] The difference between Example 9 and Example 1 is that in step (2), the thickness of the gallium nitride layer is 10 μm; the temperature for growing the gallium nitride layer is 1050° C., the pressure for growing the gallium nitride layer is 500 mbar, and the time for growing the gallium nitride layer is 1000 s.
[0167] Example 10
[0168] The difference between Example 10 and Example 1 is that in step (2), the thickness of the aluminum nitride layer is 15 nm; the temperature for growing the aluminum nitride layer is 1000° C., the pressure for growing the aluminum nitride layer is 10 mbar, and the time for growing the aluminum nitride layer is 10 s.
[0169] Embodiment 11
[0170] The difference between Example 11 and Example 1 is that in step (2), the thickness of the aluminum nitride layer is 30 nm; the temperature for growing the aluminum nitride layer is 1030° C., the pressure for growing the aluminum nitride layer is 200 mbar, and the time for growing the aluminum nitride layer is 100 s.
[0171] Example 12
[0172] The difference between Example 12 and Example 1 is that in step (3), the thickness of the organic functional group layer is 200 nm.
[0173] Example 13
[0174] The difference between Example 13 and Example 1 is that in step (3), the thickness of the organic functional group layer is 1000 nm.
[0175] Embodiment 14
[0176] The difference between Example 14 and Example 1 is that in step (3), the first solution is an ethanol solution of a boric acid functionalized carbon quantum dot molecular imprinting polymer, and the organic functional group layer is a boric acid functionalized carbon quantum dot molecular imprinting film.
[0177] Embodiment 15
[0178] The difference between Example 15 and Example 1 is that in step (3), the first solution is an ethanol solution of reduced graphene-nano copper molecular imprinting polymer, and the organic functional group layer is a reduced graphene-nano copper molecular imprinting film.
[0179] Example 16
[0180] The difference between Example 16 and Example 1 is that in step (4), the target metal is titanium; the metal electrode layer is a titanium layer, and the thickness of the titanium layer is 50 nm.
[0181] Embodiment 17
[0182] The difference between Example 17 and Example 1 is that in step (4), the target metal also includes platinum, molybdenum, iridium, tantalum, niobium, and cobalt; the metal electrode layer includes a titanium layer, an aluminum layer, a nickel layer, a gold layer, a platinum layer, a molybdenum layer, an iridium layer, a tantalum layer, a niobium layer, and a cobalt layer stacked in sequence, the thickness of the titanium layer is 30nm, the thickness of the aluminum layer is 300nm, the thickness of the nickel layer is 30nm, the thickness of the gold layer is 100nm, the thickness of the platinum layer is 50nm, the thickness of the molybdenum layer is 200nm, the thickness of the iridium layer is 40nm, the thickness of the tantalum layer is 150nm, the thickness of the niobium layer is 30nm, and the thickness of the cobalt layer is 70nm.
[0183] Embodiment 18
[0184] The difference between Example 18 and Example 1 is that in step (4), the annealing temperature is 500° C. and the annealing time is 100 s.
[0185] Embodiment 19
[0186] The difference between Example 19 and Example 1 is that in step (4), the temperature of the annealing treatment is 1000° C. and the duration of the annealing treatment is 10 s.
[0187] Comparative Example
[0188] The difference between the comparative example and embodiment 1 is:
[0189] In step (1), the original silicon substrate is ultrasonically cleaned with deionized water under constant temperature conditions to obtain a silicon substrate; the ultrasonic cleaning time is 30 minutes;
[0190] In step (2), after the silicon substrate is loaded into the MOCVD reactor, first, nitrogen (N 2 ), trimethylaluminum and trimethylindium (Trimethylindium, In(CH 3 ) 3 ) is introduced into an MOCVD reactor to generate an indium aluminum nitride (InAlN) buffer layer on any surface of the silicon substrate; then, metal gallium and nitrogen are introduced into the MOCVD reactor to grow an intrinsic gallium nitride layer on the upper surface of the InAlN buffer layer; then, a p-type gallium nitride layer is grown on the upper surface of the intrinsic gallium nitride layer; finally, metal gallium, nitrogen and trimethylaluminum are introduced into the MOCVD reactor to grow an intrinsic aluminum gallium nitride layer on the upper surface of the p-type gallium nitride layer; wherein the thickness of the InAlN buffer layer is 250nm; the temperature for growing the intrinsic gallium nitride layer is 750°C, the pressure is 100mbar, the duration is 90min, and the thickness of the intrinsic gallium nitride layer is 3μm; the temperature for growing the p-type gallium nitride layer is 500°C, the duration is 200s, and the thickness of the p-type gallium nitride layer is 5μm; the temperature for growing the intrinsic aluminum gallium nitride layer is 800°C, the pressure is 80min, and the thickness of the intrinsic aluminum gallium nitride layer is 5μm;
[0191] In step (3), a first solution is spin-coated on the upper surface of the intrinsic aluminum gallium nitride layer, and the first solution spin-coated on the upper surface of the intrinsic aluminum gallium nitride layer is dried to obtain an organic functional group layer;
[0192] In step (4), the target metal is evaporated by electron beam, a first electrode layer is deposited on a first region of the organic functional group layer, and a second electrode layer is deposited on a second region of the organic functional group layer, thereby obtaining a glucose concentration sensor.
[0193] The glucose concentration sensors prepared in Example 1, Example 14, Example 15 and the comparative example were used to detect the glucose concentration of the liquid containing glucose molecules. The detection results are as follows: Figure 4 shown.
[0194] Reference Figure 4 The glucose concentration sensor prepared in Example 1 is used to detect the glucose concentration of a liquid containing glucose molecules. The current value output by the glucose concentration sensor increases with the increase of the glucose concentration, and the linear correlation coefficient R between the current value output by the glucose concentration sensor and the glucose concentration is 1 2 It is 0.996, showing good linearity.
[0195] The glucose concentration sensor prepared in Example 14 was used to detect the glucose concentration of a liquid containing glucose molecules. The current value output by the glucose concentration sensor increased with the increase of the glucose concentration, and the linear correlation coefficient R between the current value output by the glucose concentration sensor and the glucose concentration was 2 2 It is 0.998, showing good linearity.
[0196] The glucose concentration sensor prepared in Example 15 is used to detect the glucose concentration of a liquid containing glucose molecules. The current value output by the glucose concentration sensor increases with the increase of the glucose concentration, and the linear correlation coefficient R between the current value output by the glucose concentration sensor and the glucose concentration is 3 2 It is 0.992, showing good linearity.
[0197] When the glucose concentration sensor prepared in the comparative example is used to detect the glucose concentration of a liquid containing glucose molecules, there is no obvious correlation between the current value output by the glucose concentration sensor and the glucose concentration, and the linear correlation coefficient R between the current value output by the glucose concentration sensor and the glucose concentration is 4 2 It is only 0.721, and the linearity is poor. The glucose concentration sensor prepared based on the comparative example is used to detect the glucose concentration of a liquid containing glucose molecules, and the reliability of the measured glucose concentration is low.
[0198] In summary, the current value output by the glucose concentration sensor provided in the embodiment of the present invention increases with the increase of glucose concentration, and the linear correlation coefficient between the current value output by the glucose concentration sensor and the glucose concentration is above 0.99, showing good linearity. The glucose concentration of a liquid containing glucose molecules is detected based on the glucose concentration sensor provided in the embodiment of the present invention, and the measured glucose concentration has high reliability. During the test, the relationship expression between the current value and the glucose concentration can be determined based on the linear relationship between the current value output by the glucose concentration sensor and the glucose concentration. In subsequent tests, the glucose concentration can be determined based on the current value output by the glucose concentration sensor and the relationship expression. Moreover, the glucose concentration sensor provided in the embodiment of the present invention has a simple structure and is easy to operate. While improving the detection sensitivity and reliability of the glucose concentration, it also reduces the detection cost of the glucose concentration.
[0199] The above is a detailed introduction to a glucose concentration sensor and a preparation method thereof provided by the present invention. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A glucose concentration sensor, characterized in that: The glucose concentration sensor comprises a substrate, a gallium nitride layer, an aluminum nitride layer, an organic functional group layer and a metal electrode layer; The substrate comprises at least one isosceles trapezoidal structure; adjacent isosceles trapezoidal structures are spaced by a first length; the isosceles trapezoidal structure comprises a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are waists of the isosceles trapezoidal structure; the third side surface is opposite to the fourth side surface and is perpendicular to the top surface; The gallium nitride layer is epitaxial on the first side surface and the second side surface; the aluminum nitride layer is stacked on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure; the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas, and the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined; the electrical signal is used to indicate the concentration of the glucose molecule; The organic functional group layer is stacked on the upper surface of the aluminum nitride layer; the organic functional group layer includes a first region close to the third side and a second region close to the fourth side, and the first region and the second region are spaced apart by a second length; The metal electrode layer includes a first electrode layer and a second electrode layer, the first electrode layer is stacked in the first region and extends to the aluminum nitride layer along the plane where the third side is located, and the second electrode layer is stacked in the second region and extends to the aluminum nitride layer along the plane where the fourth side is located.
2. The glucose concentration sensor according to claim 1, characterized in that: The gallium nitride layer includes a polar surface and a semi-polar surface; The polar surface is a surface parallel to the first side surface or the second side surface, and the semi-polar surface is a surface of the gallium nitride layer other than the polar surface.
3. The glucose concentration sensor according to claim 1, characterized in that: The thickness of the gallium nitride layer is 1 μm to 10 μm; the thickness of the aluminum nitride layer is 15 nm to 30 nm.
4. The glucose concentration sensor according to claim 1, characterized in that: The organic functional group layer is any one of a glucose carbon quantum dot chitosan molecular imprinted film, a boric acid functionalized carbon quantum dot molecular imprinted film and a reduced graphene-nano copper molecular imprinted film.
5. The glucose concentration sensor according to claim 1, characterized in that: The height of the isosceles trapezoidal structure is 1 μm to 5 μm.
6. The glucose concentration sensor according to claim 1, characterized in that: The thickness of the substrate is 1 μm to 200 μm; the thickness of the organic functional group layer is 200 nm to 1000 nm; and the thickness of the metal electrode layer is 50 nm to 1000 nm.
7. A method for preparing a glucose concentration sensor, characterized in that: The method comprises: Obtain a substrate; the substrate comprises at least one isosceles trapezoidal structure, and adjacent isosceles trapezoidal structures are spaced by a first length; the isosceles trapezoidal structure comprises a first side surface, a second side surface, a third side surface, a fourth side surface and a top surface; the first side surface and the second side surface are waists of the isosceles trapezoidal structure; the third side surface and the fourth side surface are opposite and perpendicular to the top surface; epitaxially growing a gallium nitride layer on the first side surface and the second side surface; An aluminum nitride layer is grown on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure, and the gallium nitride layer and the aluminum nitride layer stacked on the upper surface of the gallium nitride layer constitute a two-dimensional electron gas; the two-dimensional electron gas is used to obtain an electrical signal when the organic functional group layer and the glucose molecule are combined; the electrical signal is used to indicate the concentration of the glucose molecule; Spin coating a first solution on the upper surface of the aluminum nitride layer, and drying the first solution spin-coated on the aluminum nitride layer to obtain an organic functional group layer; the organic functional group layer includes a first region close to the third side surface and a second region close to the fourth side surface, and the first region and the second region are spaced apart by a second length; A first electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the first area and the third side are located, and a second electrode layer is deposited in an area corresponding to the organic functional group layer and the aluminum nitride layer in a plane where the second area and the fourth side are located, to obtain a glucose concentration sensor; the first electrode layer and the second electrode layer constitute a metal electrode layer of the glucose concentration sensor.
8. The method according to claim 7, characterized in that The temperature of epitaxially growing the gallium nitride layer on the first side and the second side is 1000° C. to 1050° C., the pressure is 100 mbar to 500 mbar, and the duration is 100 s to 1000 s.
9. The method according to claim 7, characterized in that: The temperature for growing the aluminum nitride layer on the upper surface of the gallium nitride layer and the top surface of the isosceles trapezoidal structure is 1000° C. to 1050° C., the pressure is 10 mbar to 200 mbar, and the duration is 10 s to 100 s.
10. The method according to claim 7, characterized in that The step of obtaining a substrate comprises: Under constant temperature conditions, anisotropically etching any one surface of the original substrate using an alkaline solution to obtain an original substrate including at least one isosceles trapezoidal structure; the temperature of the constant temperature conditions is 10° C. to 60° C., the duration of the anisotropic etching treatment is 10 min to 30 min, and the concentration of the alkaline solution is 20 wt.% to 50 wt.%; The original substrate including at least one isosceles trapezoidal structure is cleaned with a hydrofluoric acid solution to obtain a substrate; the concentration of the hydrofluoric acid solution is 10wt.% to 30wt.%, and the cleaning time is 1min to 10min.
11. The method according to claim 7, characterized in that The first electrode layer is deposited in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the first region and the third side are located, and the second electrode layer is deposited in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the second region and the fourth side are located, to obtain a glucose concentration sensor, comprising: Depositing a first electrode layer in the first region of the organic functional group layer and the region corresponding to the aluminum nitride layer in the plane where the third side surface is located by electron beam evaporation of a target metal; Depositing a second electrode layer in the region corresponding to the organic functional group layer and the aluminum nitride layer in the plane where the second region of the organic functional group layer and the fourth side face are located by electron beam evaporation of the target metal; The first electrode layer and the second electrode layer are annealed to obtain a glucose concentration sensor; the annealing environment is a nitrogen environment, the annealing temperature is 500° C. to 1000° C., and the annealing time is 10s to 100s.
Citation Information
Patent Citations
Gallium nitride sensor, preparation method and multi-sensor system
CN105424780A
Resistance-type NO2 gas sensor based on porous substrate and preparation method thereof
CN106556628A
Sensor element for detecting particles of a measuring gas in a measuring gas chamber
CN109716101A
GaN sensor for detecting glucose concentration and detection method
CN115266889A
High integrated type pH sensor
CN206573523U